Easy synthesis of new series of pteridine analogs: di- and tetra-hydropyrimido[4,5-d]pyrimidines via 5-pyrimidinecarbaldehydes - de la Torre, José M. (2014)
Pyrimidine-5-carbaldehyde derivatives, of easy access, were selected as precursors for the synthesis of mimic pteridine derivatives 5,6-dihydropyrimido[4,5-d]pyrimidines and 5,6,7,8- tetrahydropyrimido[4,5-d]pyrimidines via 4-amino-(5-aminomethyl)pyrimidine intermediates. Straightforward procedures allow a quick access to these compounds. The dihydro derivatives were prepared means of a final cyclocondensation carried out with orthoesters, catalysed by acid and assisted by microwaves irradiation under solvent free conditions. The final cyclocondensation with carbonyl compounds forming the tetrahydro derivatives was done under mild conditions, in which stereochemical induction was carried out on the building of this skeleton, and stereochemistry assignments corroborated by theoretical calculations.